2018
DOI: 10.1016/j.jacc.2018.02.076
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in Women With Heart Disease

Abstract: Pregnancy in women with heart disease continues to be associated with significant morbidity, although mortality is rare. Prediction of maternal cardiac complications in women with heart disease is enhanced by integration of general, lesion-specific, and delivery of care variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
315
5
26

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(365 citation statements)
references
References 29 publications
19
315
5
26
Order By: Relevance
“…To our knowledge, this study was the first to present Canadian population‐based trends of pregnancy rates and delivery outcomes among women of reproductive age with CHD over a period of 13 years. Indeed, several prior studies on pregnancy outcomes in women with CHD have included women already known to be pregnant, precluding estimation of pregnancy rates from the adult CHD population . In addition, Quebec provides universal health care to its resident and more than 99% of women in the province are admitted to hospital for delivery .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this study was the first to present Canadian population‐based trends of pregnancy rates and delivery outcomes among women of reproductive age with CHD over a period of 13 years. Indeed, several prior studies on pregnancy outcomes in women with CHD have included women already known to be pregnant, precluding estimation of pregnancy rates from the adult CHD population . In addition, Quebec provides universal health care to its resident and more than 99% of women in the province are admitted to hospital for delivery .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several prior studies on pregnancy outcomes in women with CHD have included women already known to be pregnant, precluding estimation of pregnancy rates from the adult CHD population. 3,4,[8][9][10]23,31 In addition, Quebec provides universal health care to its resident and more than 99% of women in the province are admitted to hospital for delivery. 32,33 Thus, outcomes described were highly representative of the underlying population.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the CARPREG I and mWHO risk prediction tools underestimated adverse events in our population, with high rates of cardiac events despite low CARPREG I and mWHO risk scores. Previous attempts to validate the CARPREG I score in other LMICs have demonstrated both over-and underestimation of risk of adverse events, likely due to the unique spectrum of disease specific to LMICs as compared to the North American cohort from which the CARPREG I score was derived [12,14]. Over half of our cases had pulmonary hypertension, a relative contraindication to pregnancy with significant maternal and neonatal risk, which is not captured in the CARPREG I score, and thus could account for underestimate of risk [8,14,17].…”
Section: Risk Predictionmentioning
confidence: 99%
“…found to be predictive of outcome but has yet to be independently validated. 16 Recent studies suggest the modified WHO classification may be superior to the CARPREG I and ZAHARA scores in predicting poor outcomes, highlighting the challenges inherent in applying and validating these risk schemes. 11,12 F I G U R E 1 Distribution of pregnancies according to CARPREG I score (n = 161), ZAHARA score (n = 160), and modified WHO classification (n = 178) F I G U R E 2 Comparison of observed cardiac events during pregnancy to predicted event rate by CARPREG I and ZAHARA scores…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…This limits misclassification bias that can otherwise occur when using ICD codes alone to compare exposures and outcomes. This study excluded pregnancies that ended in termination or miscarriage which could have resulted in a bias toward women with less complex disease and fewer medical comorbidities who completed a pregnancy; however, our population still included a high percentage of women with moderate and complex disease.The study spanned a16 year period during which time research on pregnancy outcomes in CHD grew significantly. Outcomes as a result of changes in counseling and practice could have been impacted by newer data which is not captured in our analysis.…”
mentioning
confidence: 99%